For Alma Mater: Theory and Practice in Feminist Scholarship, Paula A. Treichler, Cheris Kramarae, and Beth Stafford, eds. ... - O’Reilly, Andrea (Canadian Woman Studies/les cahiers de la femme, 1987)
Making a Difference: Feminist Literary Criticism, Gayle Greene and Coppelia Kahn, eds.